LncRNA KCNQ1OT1 Promotes EMT, Angiogenesis, and Stemness of Pituitary Adenoma by Upregulation of RAB11A. (7th April 2022) - Li, Zuowei; Ren, Rong; Wang, Lei; Wang, Zhao; Zong, Xin; Sun, Ping; Zhu, Chunmei; Guo, Mingxia; Guo, Guizhen; Hu, Guo; Wu, Ya'nan
Abstract : This study is aimed at investigating the effect and mechanism of long noncoding RNA (lncRNA) KCNQ1OT1 on pituitary adenoma (PA). The KCNQ1OT1 expression in invasive and noninvasive PA tissues was detected by real-time fluorescence quantitative polymerase chain reaction (qPCR). The effects of KCNQ1OT1 on the proliferation of PA cells, namely, GH3 and HP75, were detected by CCK-8 experiment. The Transwell assay detected the effect of KCNQ1OT1 on the invasion of GH3 and HP75 cells. The effect of KCNQ1OT1 on the clonal formation ability was detected by clonal formation experiment. The double luciferase reporter assay and the miRNA pull down assay verified the binding of KCNQ1OT1 to miR-140-5p. Meanwhile, the regulatory effect of miR-140-5p on RAB11A was verified. qPCR results showed that KCNQ1OT1 was significantly increased in invasive PA compared with noninvasive PA tissues. Knockdown KCNQ1OT1 inhibited PA cell stemness, angiogenesis, and EMT. In addition, knockdown KCNQ1OT1 inhibited the proliferation, invasion, and clonal formation of PA. miR-140-5p is the target gene of KCNQ1OT1. miR-140-5p targets RAB11A directly. RAB11A can mediate the biological effects of KCNQ1OT1. Meanwhile, lncRNA KCNQ1OT1 can promote the EMT and cellular stemness of PA. Its mechanism of action is realized by inhibiting miR-140-5p. This result can provide a molecular basis for the further study of PA.